Le monde comme écriture divine et comme expérience religieuse : le Weltbuch (1534) de Sebastian Franck - Axelle Chassagnette (L'Atelier du CRH)
This article proposes a study of the Weltbuch (Book of the World) written by Sebastian Franck and published in 1534. Frank, a prolific author, uses his many works for the sake of his spiritual thought. Although close to the Reformation, he rejects any doctrinal corpus and any established church, putting the emphasis on the way which should lead man to God. The Weltbuch, which is mainly a descriptive cosmography, relies on this same approach. By evoking the diversity of experience across the world and underling the variety of beliefs and religions, Frank shows the spiritual development of humanity which is begging constantly